2010
DOI: 10.1186/1477-7525-8-107
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms in adults are related to impaired quality of life, regardless of asthma and COPD: results from the European community respiratory health survey

Abstract: BackgroundRespiratory symptoms are common in the general population, and their presence is related to Health-related quality of life (HRQoL). The objective was to describe the association of respiratory symptoms with HRQoL in subjects with and without asthma or COPD and to investigate the role of atopy, bronchial hyperresponsiveness (BHR), and lung function in HRQoL.MethodsThe European Community Respiratory Health Survey (ECRHS) I and II provided data on HRQoL, lung function, respiratory symptoms, asthma, atop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
57
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 32 publications
9
57
1
4
Order By: Relevance
“…Our study showed found lower QoL scores in asthma patients than in the general population, which concurs with the results of other studies in this field which used different scales (10,11).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study showed found lower QoL scores in asthma patients than in the general population, which concurs with the results of other studies in this field which used different scales (10,11).…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the results of our study, a European study found significantly lower PCS scores in manual workers (11). Manual workers are more likely to be exposed to allergens than office workers (3).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Not previously examined in older adult populations, our findings build upon the evidence that experience of breathlessness alone, regardless of asthma diagnosis, is associated with poorer ratings of general health and worse health-related quality of life 38 . Therefore, future studies examining health-related quality of life should control for experience of respiratory symptoms rather than merely the presence or absence of diagnosed respiratory diseases.…”
Section: Discussionsupporting
confidence: 67%